Bis(dipyrrinato)metal(ii) coordination polymers: crystallization, exfoliation into single wires, and electric conversion ability1. Issue 5 (20th May 2015) - Matsuoka, Ryota; Toyoda, Ryojun; Sakamoto, Ryota; Tsuchiya, Mizuho; Hoshiko, Ken; Nagayama, Tatsuhiro; Nonoguchi, Yoshiyuki; Sugimoto, Kunihisa; Nishibori, Eiji; Kawai, Tsuyoshi; Nishihara, Hiroshi
<x xml:space="preserve">Abstract</x> The titled coordination polymers feature crystallization, single wire exfoliation, processability, and applicability to photoelectric and thermoelectric conversion systems.